From policy to practice: An assessment of biosecurity practices in cattle, sheep and goats production, marketing and slaughter in Baringo County, Kenya - Mutua, Edna N.; Bett, Bernard K.; Bukachi, S.A.; Estambale, B.A.; Nyamongo, I.K. (2022)
Globally, biosecurity is instrumental in prevention, control and management of livestock diseases and protection of human health. It is defined, prescribed, adopted and enforced through global, regional and national frameworks, laws, policies and strategies. There is more biosecurity practice research conducted in developed countries than developing ones. Consequently, the gap between the ideals recommended in biosecurity frameworks and what is practical in under-resourced rural settings is poorly understood. This anthropological study sought to assess adoption of biosecurity practices across a cattle, sheep and goat value chains continuum to demonstrate where risks lie. The cross-sectional mixed-methods study took place in Baringo County, Kenya. Qualitatively, it utilized 26 focus group discussions with community members and 10 observational interviews with slaughter facility workers. Quantitatively, it included a household survey with 560 community members and a separate survey with 231 livestock traders. Results show that producers, traders and slaughter facility workers did observe some biosecurity practices but not others due but not limited to personal preference, limitations in veterinary service delivery and enforcement of some biosecurity measures, and lack of requisite infrastructure. The study concludes that the implementation of biosecurity measures in rural settings is more complex than envisioned in biosecurity policies and frameworks. It can be hampered by resource limitations, poor enforcement, and contestations with cultural practices. The study recommends that further studies on willingness to adopt biosecurity measures targeting community members in under-resourced settings be conducted to identify possible critical points of intervention at county and national levels.